KREDIT (AT-TAQHSITH) DALAM DISKURSUS HADIS NABI MUHAMMAD SAW - Taufiq Sanusi Baco (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2020)
AbstractCredit in conventional banking is haram because it uses a refined usury system called interest, both credit is productive, especially consumptive based on the Alquran and the hadith of the prophet about usury that Abbas, his uncle, saw. Credit in Syari'ah banking is allowed because credit at Bank Syari'ah is transferred to mudharabah for the productive and ba'i bi at-taqshid for the consumptive based on the hadith of the Prophet Muhammad and the opinion of the scholars. Basically the whole concept of mu'amalah is permissible as long as it doesn’t contradict the principles of the Alquran and sunnah such as the ushul kaedah which means: